Poetic Void in Leśmian’s Poetry and the Biblical Desert: A Contribution to the Discussion on the Place of Difficulties in Education - Dobrosielska, Urszula (Paedagogia Christiana, 2026)
The article is a response to doubts about the fair assessment of the phenomenon of difficulties in education. In a world that is changing rapidly, it may seem that issues related to difficulty, suffering and other obstacles which are inherent in the educational process, disappear from the horizon of reflection in favor of the ‘pleasure’ of discovering knowledge. Regarding this, the text presents a search for answers to such questions as: is there still a place for ‘difficulties’ in modern education, and does difficulty in the educational process bring positive benefits to the students? The phenomenon of difficulty and the resulting suffering was analysed through the example of two literary images: the phenomenon of the desert presented in the Bible and the void presented in the poetry of Bolesław Leśmian. In the analysis of the biblical desert, several selected fragments of the Bible from the Old and New Testaments were interpreted, as well as information from the Dictionary of Biblical Theology and literature on the subject. The work The Girl by Bolesław Leśmian is the main field for leading the reflection on the phenomenon of the void in his poetry. The article presents the differences and similarities of the two analysed literary images. Conclusions emerging from the analyses and interpretations carried out in the text lead to the recognition of the value of difficulties encountered on the path of the educational process. They arise as an opportunity to transcend one’s limitations, to seek and make sense of the situations that appear, to put one’s own reality in order anew, and thus to try to understand oneself as well as one’s presence in relation to the world.